Ground-ice data, Itkillik River - Mikhail Kanevskiy; Yuri Shur (Arctic Data Center, 2015)
This dataset contains information on ground ice obtained at the Itkillik River field site in 2011-2012 by means of permafrost coring. The dataset includes the data on cryostratigraphy, ice contents, and isotope composition of various types of ground ice.